(untitled) (Revista Apotheke, 2025)
The artistic work of Salette Tavares (1922-1994) presupposes a conception of aesthetics as an expe-rience of capturing and apprehending the “matter of creation”. The artist sees in the diversification of poetics a set of resources for realizing the formal possibilities of artistic objects and grants aes-thetics, as a mode of knowledge, an active intervention in the process of conception and realization of a work of art, and not the mere explanation of this process. For the artist, the inseparable con-cepts of “form” and “creation” imply a phenomenological deepening of the place of aesthetics with-in the scope of philosophy and artistic creation, from what she envisioned to be the beginning of an era of radical experimentation in the field of arts from the 1950s and 1960s, in which creation and invention feed each other.